ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP KELAS VII DALAM MENYELESAIKAN SOAL MATERI ALJABAR - Sumartini, Tintin; Rosyana, Tina; Afrilianto, M. (IKIP Siliwangi, 2023)
A learning models that demanding activity of student to understand the concept of learning situations and problems presented is the model Problem Solving. The purposes of the research is to analyze the problem solving ability of student junior high schoolin solving aljabar test,the ability that hoped might by students is solving math test ability. This research is classroom action research in two siklus. This research the subjects in were students of class VII A SMP Al-Mahmud Plus in the odd semester of the 2021/2022 school year, totaling 21 people. Data instruments were the observation sheet and test questions. The instrument used consists of 5 question with each question consisting of 4 indicators of abilitiy.Data analysis of research is technique using Microsoft excel in the form of descriptive statistics. From data analysis of Research data is shows 66 % of the students are able to understand the problem in the instrument tes, 60% students can plan completion, 57% of students can run a completion plan and 40 % students can check back.